2016
DOI: 10.1063/1.4943007
|View full text |Cite
|
Sign up to set email alerts
|

Generation of micro-sized PDMS particles by a flow focusing technique for biomicrofluidics applications

Abstract: Polydimethylsiloxane (PDMS), due to its remarkable properties, is one of the most widely used polymers in many industrial and medical applications. In this work, a technique based on a flow focusing technique is used to produce PDMS spherical particles with sizes of a few microns. PDMS precursor is injected through a hypodermic needle to form a film/reservoir over the needle's outer surface. This film flows towards the needle tip until a liquid ligament is steadily ejected thanks to the action of a coflowing v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 38 publications
1
68
0
Order By: Relevance
“…Recent microfluidic and micro-electro-mechanical systems (MEMS) have demonstrated that the high elasticity (flexibility) of polydimethylsiloxane (PDMS) offers unique advantages over more traditional rigid substrate materials such as glass and harder polymers [1,4] . Thus, PDMS has become the most widely used siliconbased organic polymer due to its unique mechanical and optical properties, and is generally considered inert, non-toxic and non-flammable, among other characteristics [3,[5][6][7] . Its applications range from contact lenses and medical devices to shampoos, caulking, lubricating oils and heat-resistant tiles [3,6] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent microfluidic and micro-electro-mechanical systems (MEMS) have demonstrated that the high elasticity (flexibility) of polydimethylsiloxane (PDMS) offers unique advantages over more traditional rigid substrate materials such as glass and harder polymers [1,4] . Thus, PDMS has become the most widely used siliconbased organic polymer due to its unique mechanical and optical properties, and is generally considered inert, non-toxic and non-flammable, among other characteristics [3,[5][6][7] . Its applications range from contact lenses and medical devices to shampoos, caulking, lubricating oils and heat-resistant tiles [3,6] .…”
Section: Introductionmentioning
confidence: 99%
“…Droplet generation may be driven using active methods such as piezoelectric actuators and electric fields [15][16][17] , but monodisperse droplets are most commonly formed in continuous pressuredriven nozzles with flow-focusing or co-flowing method [7,16,[18][19][20] , or T-junction techniques [21][22][23] . Jian et al [24] and Muñoz-Sánchez et al [7] proposed a flow-focusing technique where a PDMS precursor was dispersed into microdroplets within a continuous phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the particles used in the literature for similar studies 34,38,39,41 are rigid or semi-rigid and larger; this is an important issue regarding the development of two-phase analogue fluids because it is extremely difficult to develop deformable micron-sized particles in a considerable quantity to make blood analogue fluids. By using a flow focusing technique, Munoz-Sanchez et al 51 were able to produce a limited amount FIG. 3.…”
Section: Deformability Analysismentioning
confidence: 99%
“…Within the 24 publications cited by this literature search for microfluidics applied to industrial biotechnology: seven of them are patents related to microfluidic devices for the chemical, pharmaceutical, and biotechnological industries; two are conference articles about biosensors, and another six articles involve mass flow sensor, nanoimprint lithography, perspectives for microalgae exploitation and marine biotechnology, generation of PDMS microparticles, or liposomes . Therefore, it remains only nine publications regarding industrial biotechnology, specially involving cells separation systems, microbioreactors, enzymatic reactions, bacterial culture, capillary systems for fluid treatment, techniques for biological applications, and, finally, a review concerning bioproduction systems …”
Section: Introductionmentioning
confidence: 99%